Sofosbuvir plus ribavirin for treatment of hepatitis C virus in patients co-infected with HIV (PHOTON-2): a multicentre, open-label, non-randomised, phase 3 study. Issue 9973 (21st March 2015) - Molina, Jean-Michel; Orkin, Chloe; Iser, David M; Zamora, Francisco-Xavier; Nelson, Mark; Stephan, Christoph; Massetto, Benedetta; Gaggar, Anuj; Ni, Liyun; Svarovskaia, Evguenia; Brainard, Diana; Subramanian, G Mani; et al.
Summary: Background: Although interferon-free regimens are approved for patients co-infected with HIV and genotype-2 or genotype-3 hepatitis C virus (HCV), interferon-based regimens are still an option for those co-infected with HIV and HCV genotypes 1 or 4. These regimens are limited by clinically significant toxic effects and drug interactions with antiretroviral therapy. We aimed to assess the efficacy and safety of an interferon-free, all-oral regimen of sofosbuvir plus ribavirin in patients with HIV and HCV co-infection. Methods: We did this open-label, non-randomised, uncontrolled, phase 3 study at 45 sites in seven European countries and Australia. We enrolled patients (aged ≥18 years) co-infected with stable HIV and chronic HCV genotypes 1–4, including those with compensated cirrhosis. Once-daily sofosbuvir (400 mg) plus twice-daily ribavirin (1000 mg in patients with bodyweights <75 kg and 1200 mg in those with weights ≥75 kg) was given for 24 weeks to all patients except treatment-naive patients with genotype-2 HCV, who received a 12-week regimen. The primary efficacy endpoint was sustained virological response 12 weeks after treatment. We did analysis by modified intention to treat. This study is registered withClinicalTrials.gov, numberNCT01783678 . Findings: Between Feb 7, 2013, and July 29, 2013, we enrolled 275 eligible patients, of whom 262 (95%) completed treatment; 274 patients were included in the final analysis. Overall rates of sustained virological response 12 weeks after treatment were 85% (95% CI 77–91) in patients with genotype-1 HCV, 88% (69–98) in patients with genotype-2 HCV, 89% (81–94) in patients with genotype-3 HCV, and 84% (66–95) in patients with genotype-4 HCV. Response rates in treatment-naive patients with HCV genotypes 2 or 3 (89% [95% CI 67–99] and 91% [81–97], respectively) were similar to those in treatment-experienced patients infected with those genotypes (83% [36–100] and 86% [73–94], respectively). There was no emergence of sofosbuvir-resistance mutations in patients with HCV viral relapse. Six (2%) patients discontinued treatment because of adverse events. The most common adverse events were fatigue, insomnia, asthenia, and headache. Four (1%) patients had serious adverse events regarded as related to study treatment. Additionally, four (1%) patients receiving antiretroviral treatment had a transient HIV viral breakthrough; however, none required changes in antiretroviral regimen. Interpretation: Sofosbuvir and ribavirin provided high rates of sustained virological response after 12 weeks of treatment in treatment-naive and treatment-experienced patients co-infected with HIV and HCV genotypes 1–4. The characteristics of this interferon-free combination regimen make sofosbuvir plus ribavirin a useful treatment option for this patient population. Funding: Gilead Sciences.